Readers’ reception trend in accepting Ian McEwan novels in Mainland China: a systematic review - Wen, Nie; Abang Abai, Dayang Shobihah; Chan, Siaw Leng; Mohd Isa, Nur Ayuni (Human Resource Management Academic Research Society, 2024)
In the context of rapid globalization and heightened cultural exchange, cross-cultural translation and literary reception have emerged as critical areas of inquiry within contemporary literary studies. This review investigates the trends in the reception of Ian McEwan’s novels among readers in mainland China. A systematic analysis was conducted using databases such as CNKI, EBSCO, Web of Science, Taylor and Francis, and Science Direct, focusing on twenty scholarly articles published between 2000 and 2024. Employing content analysis as the primary methodological framework, the findings indicate a significant gap in studies addressing the reception of McEwan’s works by general readers. Notably, only a limited number of novels—specifically Saturday, Amsterdam, The Cement Garden, The Comfort of Strangers, and Atonement—have achieved considerable acceptance among Chinese audiences since 2014. These insights contribute to a nuanced understanding of the reception dynamics of Western literary texts in a non-Western context, offering valuable perspectives for literary scholars and researchers.